Data analysis by factorial methods: application to sexually transmitted diseases for the provincial division of Health (DPS) of Central Kasai - MUTOMBO NTUMBA, Jean (Revue Internationale du Chercheur, 2025)
Abstract This article analyzed, by factorial methods, sexually transmitted diseases (MST) which constitute a public health problem in the province of Central Kasai, in the Democratic Republic of Congo. MST are infectious, contagious diseases, very diverse etiologies through unprotected sexual contacts, whether vaginal, anal or oral. They can be caused by bacteria, viruses or parasites; and can various symptoms or be asymptomatic which makes their early detection significant to avoid serious complications. After the main component analysis (ACP), the most affected health areas are: Masuika, Tshibala, Kananga, Katende, Mikalayi, Bena tshiadi, Bena Leka and Luambo, among the 26 health areas of the provincial health division of Central Kasai. Research suggests carrying out awareness through organizations with community Assisi and other communication channels to effectively fight this phenomenon in the province of Central Kasai.